Estudo metabolômico da interação planta-fungo endofítico por RMN de 1H - Lacerda, Jhuly Wellen Ferreira (2020)
The plant and endophytic fungi interaction may change quantitative and qualitatively the plant metabolomics. Although the plant metabolism consists of a dynamic system, which involves the production of primary and secondary metabolites, the variation in the levels of some metabolites reflected directly in the production of others. The investigation of plant metabolism has been performed quickly and robustly through metabolomic in the last 5 years. Metabolomics is a strategic tool used to explore a chemical composition of complex matrices, using mainly techniques such as mass spectrometry (MS) and nuclear magnetic resonance (NMR). In this context, Combretum lanceolatum plants were cultivated in vitro and inoculated with endophytic fungi Diaporthe phaseolorum (Dp) and Trichoderma spirale (Ts), and the plant chemical composition was evaluated at 0, 1 and 7 days contact. The NMR analyses were performed using deuterated water (D2O) with 0.05% TSP. The 1H NMR data were processed using the softwares and database, furnishing 132 metabolites, that were identified and quantified. Plants inoculated with Dp showed different chemical profile since the initial contact phase (0 day), indicating an increase of biotin concentration. After 1 day and 7 days of inoculation, seven and twelve metabolites were identified on plant metabolomics, respectively. The data obtained from 1H NMR spectra were explored by multivariate analyzes of PCA and PLS-DA. The PCA analyses showed a variation of 71.4% of the data included by the first two components. The discrimination study of the groups formed by PLS-DA for Dp demonstrated a selection of 2 classes, where together as 2 previous components 60, 52 and 66% of the total variation of the data at times 0, 1 and 7 days, respectively. The plants inoculated with Tsshowed metabolomics changes only at 7 days of interaction, providing an increase of L-Carnitine and statistically 60.8% of the variation of data for PCA was observed. Thus, the interaction of C. lanceolatum with endophytic fungal Ts and Dp shows quantity and quantity differences in the plant metabolism over interaction time.